Current challenges of research on filamentous fungi in relation to human welfare and a sustainable bio-economy: a white paper. Issue 1 (December 2016) - Meyer, Vera; Andersen, Mikael; Brakhage, Axel; Braus, Gerhard; Caddick, Mark; Cairns, Timothy C.; Vries, Ronald; Haarmann, Thomas; Hansen, Kim; Hertz-Fowler, Christiane; Krappmann, Sven; Mortensen, Uffe; et al.
Abstract The EUROFUNG network is a virtual centre of multidisciplinary expertise in the field of fungal biotechnology. The first academic-industry Think Tank was hosted by EUROFUNG to summarise the state of the art and future challenges in fungal biology and biotechnology in the coming decade. Currently, fungal cell factories are important for bulk manufacturing of organic acids, proteins, enzymes, secondary metabolites and active pharmaceutical ingredients in white and red biotechnology. In contrast, fungal pathogens of humans kill more people than malaria or tuberculosis. Fungi are significantly impacting on global food security, damaging global crop production, causing disease in domesticated animals, and spoiling an estimated 10 % of harvested crops. A number of challenges now need to be addressed to improve our strategies to control fungal pathogenicity and to optimise the use of fungi as sources for novel compounds and as cell factories for large scale manufacture of bio-based products. This white paper reports on the discussions of the Think Tank meeting and the suggestions made for moving fungal bio(techno)logy forward.